Trust in E-services technologies, practices and challenges - Song, Ronggong; Korba, Larry (Hershey, Pennsylvania Idea Group Publishing, 2007)
Provides an overall view of trust for e-services including definitions, constructs, and relationships with other research topics such as security, privacy, reputation and risk. Offers contributions from real-life experience and practice on how to build a trust environment for e-government services.
Trust concepts and challenges in E-services -- Trust technologies in E-services -- Trust practices in E-services.
Keywords: Electronic commerce -- Security measures; Web services; Trust; Computer systems -- Reliability; Internet in public administration; Electronic books